The Role of CSR (Corporate Social Responsibility) in reducing Reputation Risk due to Covid-19 For Islamic Financial Institutions in Indonesia - Ekawati, Wiwin Erna; Manora, Novfitri Landong (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Purpose - This study aims to analyze the effect of CSR programs carried out by Islamic banking companies on reducing reputation risk by covid 19.Method - This study uses a literature study approach to answer the research objectives. The literature study conducted in this research is a form of research conducted by collecting journal articles with themes according to the research objectives, namely reviewing the definition and importance of implementing reputation risk management in Islamic Financial Institutions.Result - The result of this research indicates that Islamic banks have a higher reputation risk than conventional banks because apart from looking at the operational aspects, the public also sees the spiritual aspects of Islamic banks in carrying out their operations.Implication - This study uses the data from scientific journal articles available online with the help of search engines, google scholar. Source of data derived from two sources, namely: primary data derived from journals on Islamic Economics, Islamic Corporate Social Responsibility and articles on covid -19, as well as reliable readings that can support this research.Originality- Relaxation of financing facilities for customers affected by the Covid-19 virus pandemic in the form of postponement of payments and/or granting of margin/profit sharing relief whose terms and conditions are adjusted to the economic sector, criteria, and customer conditions while still referring to OJK regulations.